OPTIMALISASI PELAYANAN DAN PENANGANAN KASUS SEXTING PADA REMAJA DI KOTA TASIKMALAYA - Peni Cahyati; Nunung Mulyani; Kusmiyati; Heri Djamiatul (LP4M STIKes Karsa Husada Garut, 2022)
Sexual violence is currently increasing with the development of internet-based technology media access, technology products, and various applications and social media. The forms of sexual violence that often occur today are changing in digital form which is manifested in the language of communication in the routine of social interaction. This form of sexual violence is known as sexting. The term sexting refers to the sending and receiving of sexually explicit images through some form of virtual messaging, where a person sends messages or materials in the form of explicit images and videos electronically, especially through mobile phones, the internet and other electronic media. The growth in the number of teenage victims of online crime is very rapid, the number of internet users and many teenagers are irresponsible in using social media technology, especially in text. This can be seen from the survey results that eight out of ten teenagers say they have had sex by sexting. In the city of Tasikmalaya, complaints of student sexting are found every year to the Integrated Service Center for the Protection of Women and Children, so that effective services and handling are needed in preventing sexting and assisting victims of adolescent sexting. The activity was carried out in a series of community service science and technology for the community (IbM) Tasikmalaya Health Polytechnic. The activity will be carried out within 1 year.